Evaluasi Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK 3) pada Proyek Preservasi Jalan Simpang Siak Sri Indrapura – Mengkapan/Buton (MYC) di Kabupaten Siak - Ahmad Rivin Damanik; Zaid Perdana Nasution; Gina Cynthia R Hasibuan (Jurnal Syntax Admiration, 2022)
Occupational safety and health is an instrument that protects workers, companies, the environment, and the surrounding community from hazards due to work accidents. This protection is a human right that must be fulfilled by the company. K3 aims to prevent, reduce, even eliminate the risk of work accidents (zero accident). In the field of construction services, there are many problems regarding the not yet optimal implementation of the Occupational Safety and Health Management System (SMK3), while the implementation has not been optimal due to several factors. One of the activities that influence the success of the job is the capacity and capability of the service provider. Evaluation of service provider performance appraisal is the process of measuring, analyzing, and managing provider performance with the aim of reducing costs, reducing risk and directing continuous improvement in value and operations. This study seeks to evaluate the performance of service providers in implementing SMK3 based on the SMK3 Implementation Criteria using the AHP (Analytical Hierarchy Process) method. The research location is the Siak Sri Indrapura - Meng Kapan / Buton (MYC) Simpang Siak Road Preservation project in Siak Regency, Riau Province which is one of the construction projects that has a high risk of work accidents.